Purificação e caracterização físico-química de proteínas e peptídeos obtidas a partir das vísceras do peixe peroá branco (Balistes capriscus) - Balderrama, Maribel Cárdenas (2021)
Peroá branco (Balistes capriscus) is a fish that presents a wide distribution throughout the Atlantic coast, being valued for both commercial and recreational fishing. Its meat is considered of excellent quality and is characterized by having a high nutritional theory. For about 30% of the body (viscera, skin and scales) is not used by the fish processing industries, generating a high protein residue. It is of biotechnological interest to the application of proteins and, for this, it is necessary or studied of their physical-chemical characteristics for a better industrial use. We have studied the proteins obtained from fish waste, but they are extracted and purified, as they differ in molecular mass and charge, characterized in relation to their amidase, esterasic and conformational state activity. Proteins were extracted by chemical extraction with sodium hydroxide and hydrochloric acid, followed by molecular exclusion chromatography using Sephadex G-200 gel column. As molecular masses of the fractions determined by SDS-PAGE and stayed in the range of 160 kDa and 16 kDa. As the purified protein fractions "E" and "F" form at least in alkaline pH at pH 7.5, using BApNA as same fractions catalyzed or TAME substrate no pH 6.0 and 8.0. A similar profile of enzymatic activity was observed as fractions of purified proteins by ionic exchange (cationic) chromatography. Or check the “half-life” quality of the gross protein extract, which, at 4oC, maintains its biological activities for less than six months. A method of purification and characterization of proteins and peptides from fish waste peroá branco (Balistes capriscus) showed satisfactory, it was possible to purify high quantities of crude protein extract of 18 mg até 150 mg with separation in protein and peptide fractions as a satisfactory resolution.